Selection of mercury accumulator plants for gold mine tailing contaminated soils - N Muddarisna; B D Krisnayanti (Brawijaya University, 2015)
Phytoremediation, which is more efficient with less side effects than conventional physical and chemical methods, is increasing in popularity as a remediation system. This paper provides a brief overview of developments in research and application of phytoremediation of soil contaminated with gold mine tailings containing mercury. Lindernia crustacea L., Digitaria radicosa Presl. Miq., Zingiber purpurium L, Paspalum conjugatum Berg., Cyperus kyllingia Endl., and Caladium bicolor Vent., that were selected for this study were planted in the planting media consisting of soil (70%) and tailings (30%) for 9 weeks. The results showed that after 9 weeks of planting, Paspalum conjugatum had growth rate, biomass production, Hg accumulation, and ratio of shoot Hg : root Hg higher than those of other plant species tested, both in the media consisted of amalgamation and cyanidation tailings. It can thus be concluded that Paspalum conjugatum is potential plant species for remediating mercury-contaminated soil.